Specific Far Infrared Spectroscopic Properties of Phospholipids. Issue 5 (11th July 2012) - Hielscher Hielscher, Ruth Ruth; Hellwig Hellwig, Petra Petra
Abstract : We describe the specific spectral signature of different phospholipids and sphingolipids in the far infrared. Three specific spectral domains have been found: the head group contributions (600 and 480 cm −1 ); the modes of the torsion motion of the hydrocarbon chains and of the skeleton vibration (460 to 180 cm −1 ); and the hydrogen-bonding continuum (below 300 cm −1 ). Marker bands for individual phospholipids are distinguished.